The Mutqin Method: Implementation of Learning to Memorize the Qur'an in Islamic Boarding Schools - Salahuddin, Salahuddin; Fadlilah, Fadlilah; Fitriani, Suci; Chaniago, Fransisko; Utama, Gusneli (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2024)
In general, there are many familiar methods used in memorizing the Qur'an, such as the tahfiz method, the wahdah method, the kitabah method, the combined method, the jama' method, the talaqqi method, the Jibril method, and the takrir method. The Mutqin method is a combination of several methods used in the process of memorizing the Qur'an. This research is motivated by the condition of ability to memorize the Qur'an at the Tahfidz Satu Qur’an Islamic Boarding School, Jambi. With the mutqin method applied at the Tahfidz Satu Qur’an Islamic Boarding School Jambi, it can help in memorizing the Al-Qur'an. The purpose of this study was to examine the process of implementing the Mutqin method in memorizing the Qur'an at the Tahfidz Satu Qur’an Islamic Boarding School, Jambi. This study uses a descriptive qualitative research approach in the form of words or direct interviews with the Tahfidz Satu Qur’an Islamic Boarding School caretaker in Jambi which includes the process of implementing the mutqin method to memorize the Qur’an. The results showed that the process of implementing the mutqin method in memorizing the Qur'an at the Tahfidz Satu Qur’an Islamic Boarding School, Jambi, had gone well. With three stages namely, preparation before memorization, application of memorization deposit and memorization evaluation